Hospital care for the elderly in the final year of life: a population based study. Issue 6742 (7th July 1990) - Henderson, J; Goldacre, M J; Griffith, M
Abstract : OBJECTIVES--To determine whether among people aged 65 and over those who died at advanced old age spent more of their last year of life in hospital than those who died younger, and whether the increase in longevity in the elderly between 1976 and 1985 was accompanied by increased time spent in hospital in the last year of life. DESIGN--Linkage of death records to abstracts of records of hospital inpatient care in the preceding year of patients' lives. SETTING--Six health districts in England covered by the Oxford record linkage study. RESULTS--People who died at advanced ages (85 and over) were less likely than people who died at younger ages (65-84) to have been admitted to hospital in the last year of life. Once admitted the very old tended to spend longer in hospital than others. The mean total time spent in hospital by the elderly in the year before death (based on all deaths including those among people not admitted at all) showed no appreciable change over time. The median time in hospital based on all deaths increased by about three days between 1976 and 1985. During that time there was a gain in life expectancy in the population of about one year from the age of 65. CONCLUSION--The gain in life expectancy in this population was not at the expense of any substantial increase in time spent in hospital in the final year of life.